CoolAir: Temperature- and Variation-Aware Management for Free-Cooled Datacenters - Goiri, Íñigo; Nguyen, Thu D.; Bianchini, Ricardo (Proceedings of the ACM International Conference on Architectural Support for Programming Languages and Operating Systems (ASPLOS), 2015)
Despite its beneﬁts, free cooling may expose servers to high absolute temperatures, wide temperature variations, and high humidity when datacenters are sited at certain locations. Prior research (in non-free-cooled datacenters) has shown that high temperatures and/or wide temporal temperature variations can harm hardware reliability. In this paper, we identify the runtime management strategies required to limit absolute temperatures, temperature variations, humidity, and cooling energy in free-cooled datacenters. As the basis for our study, we propose CoolAir, a system that embodies these strategies. Using CoolAir and a real free cooled datacenter prototype, we show that effective management requires cooling infrastructures that can act smoothly. In addition, we show that CoolAir can tightly manage temperature and signiﬁcantly reduce temperature variation, often at a lower cooling cost than existing free-cooled datacenters. Perhaps most importantly, based on our results, we derive several principles and lessons that should guide the design of management systems for free-cooled datacenters of any size.